(3JMaI GdSGdcjfs - (3TeS GdOjf GdSefhOjs ((3ESeGYjd CafOi CcjGSi GdMfai GdcQOi s)
(3ChdgG (B:s
,(3HYO abO SCdfi HYV GdeMHjf QRbfi Gddg hEjGge Gdjbjf hGdhUhd Edi ebGe GdJecjf Cf CLeY TF eeG jMJGLg GdQGZH ai Sdhc GdWQjb hefGRd Cgd GdJMbjb s
(3BNQgG (B:s
(3hdG jDKQ ai GdaQb HjfgeG GTJQGcgeG ai GddWGaI aGage GdQehR ef GddahR JaJM dc GdcfhR hai gPG GdbOQ caGjI def habg Gddg hGdMeO ddg s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JUha JjehQ (B170) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs